Efeitos da exposição crônica ao cloreto de cádmio sobre a reatividade vascular e pressão arterial de ratos - Pereira, Camila Almenara Cruz (2013)
Cadmium is a highly toxic metal present in phosphate fertilizers, which have contributed to the cadmium contamination of food, but mostly of tobacco leaves, which makes the cigarette smoke the main source of non-occupational exposure to cadmium. Once absorbed, cadmium accumulates in the tissues, leading to many disorders such as diabetes, bone demineralization, and cancer. Furthermore, exposure to cadmium has been associated to the development of hypertension, endothelial dysfunction and atherosclerotic, process that occurs primarily in the aorta. The mechanisms involved in the changes induced by cadmium on the cardiovascular system have not been well elucidated. Thus, the aim of this study was to evaluate the effects of chronic exposure to low concentrations of cadmium chloride on blood pressure and vascular reactivity of isolated segments of rat thoracic aorta. The animals received distilled water (control group) or CdCl2 solution 100 mg/L (group Cadmium) for thirty days via drinking water. Systolic blood pressure of the animals was measured weekly by tail plethysmography. At the end of treatment, the blood cadmium content was established, and the vascular reactivity of the isolated aorta to phenylephrine, acetylcholine and sodium nitroprusside was analyzed in the context of endothelium denudation and incubation with L-NAME, apocynin, losartan, enalapril, superoxide dismutase (SOD) or catalase. The cadmium blood concentration in exposed-animals (40.3 ± 2.0 µg /L) were similar to those found in exposed workers. The rats exposed to cadmium showed an increase on systolic blood pressure since the seventh day of treatment to the fourth week. We observed an increased response to phenylephrine in rings from cadmium-rats. This increase was abolished by SOD or catalase incubation. Apocynin incubation reduced the phenylephrine response in both treatment groups, but its effect was greater in cadmium-treated rats, and NOX2 expression was greater in the cadmium group. Also, the block of NO production increased reactivity to phenylephrine in both groups, but this effect was minor on group cadmium. A similar result was found after removal of endothelium. These data suggest that cadmium in blood concentrations similar to those found in occupationally exposed 23 populations is able to stimulate NOX2 expression, contributing to oxidative stress and reducing NO bioavailability. Also, cadmium exposure seems to promote endothelial damage that might contribute to inflammation, vascular injury and the development of atherosclerosis.